2020
DOI: 10.1136/bmjdrc-2019-001122
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the risk of future diabetic foot ulcer occurrence: a prospective cohort study of patients with diabetes in Tanzania

Abstract: ObjectivesThe aim of this study was to identify the parameters that predict the risk of future foot ulcer occurrence in patients with diabetes.Research design and methods1810 (male (M)/female (F): 1012/798) patients, with no foot ulcer at baseline, participated in this study. Data from a set of 28 parameters were collected at baseline. During follow-up, 123 (M/F: 68/55) patients ulcerated. Survival analyses together with logistic regression were used to identify the parameters that could predict the risk of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 49 publications
16
29
1
Order By: Relevance
“…A number of parameters (HR [95%CI]) were found to be associated with the risk of amputation. Neuropathy (6.415 [1.119–36.778]), as in our previous study, 25 we found neuropathy as one of the main risk factor for ulceration, which is also associated with risk of amputation as was indicated in the systematic review of patients with end‐stage renal failure. 26 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A number of parameters (HR [95%CI]) were found to be associated with the risk of amputation. Neuropathy (6.415 [1.119–36.778]), as in our previous study, 25 we found neuropathy as one of the main risk factor for ulceration, which is also associated with risk of amputation as was indicated in the systematic review of patients with end‐stage renal failure. 26 …”
Section: Discussionsupporting
confidence: 82%
“…A number of parameters (HR [95%CI]) were found to be associated with the risk of amputation. Neuropathy (6.415 [1.119-36.778]), as in our previous study, 25 we found neuropathy as one of the main risk factor for ulceration, which is also associated with risk of amputation as was indicated in the systematic review of patients with end-stage renal failure. 26 PAD (9.741 [1.932-49.109]); that is in line with the previous study in which the participants with a history of PAD, were found to have 23.06 times the risk of amputation compared with those with no history of PAD when they followed for a median of 36 months.…”
Section: Association With the Risk Of Amputationsupporting
confidence: 82%
“…Of clinically related factors, duration of DM, 28,37 increased body mass index (BMI), 31,37 increased hemoglobin A1c (HgbA1c), 33,38 higher low-density lipoprotein (LDL), higher triglyceride level, and lower high-density lipoprotein (HDL) level [39][40][41][42] are associated with increased risk for vascular complication including DFU. Comorbidities like retinopathy, 23,43 nephropathy, 23,37,41,44 and neuropathy 31,[45][46][47][48] are also associated with an increased risk of having DFU.…”
Section: Introductionmentioning
confidence: 99%
“…Cognizance is raised to the clinical fact that vibration perception and touch-pressure sensation tests are important in assessing the risk of developing diabetic foot lesions, 48 and it has been reported that the combination of vibration testing using a tuning fork and touch-pressure testing using an SWM provides results that are comparable to those of the International Consensus on the Diabetic Foot. 49 In these reports, the conventional vibration testing method was used.…”
Section: Discussionmentioning
confidence: 99%